The Relationship Sexual Satisfaction and the Marital burnout in Married Women of Yasouj City - Soghra Moteshafie; Mansoureh Jamshidimanesh; Shima Haghani (نشریه پرستاری ایران, 2023)
Background & Aims Sexual dissatisfaction in women has several consequences. Due to the cultural factors and the traditional context of Iranian cities, there are limitations for women to talk about sexual issues and do not express their sexual satisfaction during the necessary care in reproductive age. This study aims to determine the relationship between sexual satisfaction and marital burnout of women living in Yasuj, Iran. Materials & Methods This cross-sectional study was conducted on 300 married women referred to four comprehensive health centers in Yasuj. Data was collected using a demographic form, the Married Women’s Sexual Satisfaction Questionnaire (MWSSQ), and the Couple Burnout Measure (CBM). The data was analyzed using the Pearson correlation test in SPSS software, version 22. Results The component of mental and physical barriers to sexual satisfaction had a significant positive correlation with the total score of CBM (r=0.488, P<0.001). Other three components of MWSSQ, including antecedents (r=-0.624, P<0.001), husband-related factors (r=-0.662, P<0.001), and dominant cultural values (r=-0.447, P<0.001) had a significant negative correlation with the total score of CBM. Conclusion Higher mental and physical barriers to sexual satisfaction can cause higher marital burnout in women, while lower antecedents, husband-related factors, and cultural values related to sexual performance can reduce marital burnout. Healthcare workers working in health centers should check women's sexual satisfaction status and, if necessary, remove their mental and physical barriers to sexual satisfaction and improve their physical, mental, and emotional conditions and relationships with husbands by providing training and counseling to them.